The Efektivitas Sari Kurma Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Nifas di Wilayah UPT Kereng Bangkirai Kota Palangka Raya - Yessica Harnetacia Tandja (Politeknik Kementerian Kesehatan Banjarmasin, 2020)
ABSTRACT Background: Anemia in postpartum women (postpartum) is also common, around 10% and 22% occur in post partum women. Anemia occurs when hemoglobin levels in the blood are low. To reduce the post partum anemia rate can be done by increasing hemoglobin levels, one of which is by consuming palm juice which can increase hemoglobin levels. Objective: This study is to determine the effectiveness of date palm juice on increasing hemoglobin levels in puerperal mothers in UPT Kereng Bangkirai Health Center in 2020. The research method used is Pre Experimental, One Group Pretest - Posttest design (one group pretest - posttest). The sampling technique used was Consecutive Sampling with a sample of 30 respondents who had met or met the inclusion criteria. The statistical test used is the T-Paired test. The result is that the postpartum hemoglobin level before giving the lowest intervention is 9.0 gr% and the highest is 11.7gr%, then after being given the intervention, the lowest hemoglobin level in the postpartum mother is 11.8gr% and the highest is 14.7gr%. In the T test, obtained p-value of 0,000 or p-value <α (0.005), this shows that there is an influence or effectiveness before and after administration of palm juice to increase hemoglobin levels in postpartum mothers. Conclusion: There is effectiveness before and after administration of date palm juice to increase hemoglobin levels in postpartum mothers in the UPT area of ​​the Kereng Bangkirai Health Center in Palangka Raya City.